Characterization of Key Sexually Dimorphic Regulators in Pain Processing - Shahrzad Ghazisaeidi; Arun Ramani; Parisa Shooshtari; Amy Tu; Katherine Halievski; David Finn; Sofia Assi; Milind Muley; Vivian Wang; Ameet Sengar; Rosanna Weksberg; Michael Brudno; et al. (Taylor & Francis Group, 2019)
Introduction/Aim: Chronic pain affects 1 in 5 Canadians and costs over $43B annually, yet effective and safe treatment options remain elusive. Recent discoveries have brought to the forefront sex differences in mechanisms of pain as a potential explanation why novel pre-clinical therapeutics have not translated into successfully in clinical trials. Methods: To begin understanding how males and females differ in pain processing, we analyzed gene expression, using RNA sequencing, and DNA methylation, using reduced representation bisulfite sequencing (RRBS), in rodent models of neuropathic pain. Results: Across both sexes, our data reveals peripheral nerve injury (PNI) caused upregulation of 61 genes involved in innate immune responses in spinal cord. In females specifically, we observed PNI-induced downregulation of 5 genes involved in neuronal function and upregulation of two classes of Cathepsins. (C and E). On the other hand, in males, we observed upregulation of 14 genes including those involved in metabolism of purines and glutathione. Additionally we found that PNI leads to methylome remodeling in a sexually dimorphic manner: 125 promoters in rat spinal cord that were differentially methylated in injured males versus females. Discussion/Conclusions: Our data shows robust sex specific DNA methylation and transcriptome signature after PNI. Additionally, our findings leads to the hypothesis that remapping of DNA methylation, with subsequent alterations in the transcriptome, are critically involved in the development of neuropathic pain. We anticipate that future research directed at understanding these differences may lead to effective drug development to combat chronic pain.